Pengaruh Pemberian Pakan Berbeda terhadap Pertumbuhan Belut Sawah (Monopterus Albus) yang dipelihara di Dalam Tong Effect of Different Feed Types on The Growth of Fresh water Ells (Monopterus albus) Kept in The Barrel - Firdaus Rezeki Manurung; Eri Yusni; Indra Lesmana (AQUACOASTMARINE, 2015)
Ells (Monopterus albus) is freshwater fishery commodities however important economic value, because it was the selling power, especially in export markets. The feed is an important factor in ell aquaculture. Research conducted to determine the effect of different feeding on growth and survival of ells. Ells maintenance container using palstic barrels with a volume of 200 liters. Experimental design using a completely randomized design with 2 treatment and 1 control, 4 replications in each treatment described as follows; 1) Giving Tubifex worms (Tubifex sp.) with pelet feed, 2) Giving snails (Pomaceae canaliculata Lamarck) with pelet feed, 3) Giving pelet feed as a control. Experiment was conducted from May until June 2014 in the backyard of the house on Setiabudi street Medan. The results showed the differences in the type of feed effect (p<0,01) on the growth of heavy and long Monopterus albus. The survival rate was 100 % in each treatment. Result showed that the snail was better than Tubifex sp. with regard to growth and conformation. Mean values with Feeding the snails (Pomaceae canaliculata Lamarck) and pellets were attained as follows: highest body length (L) 20,43 cm, body weight (W) 26,82 g,Tubifex sp. showed highest body length (L) 20,12 cm, body weight (W) 26,95 g.Keywords : Ells (Monopterus albus), Feed, Tubifex, Pomaceae canaliculata, pelet.